The European Scallop Fisheries for Pecten maximus, Aequipecten opercularis, Chlamys islandica, and Mimachlamys varia - Duncan, P F; Brand, Andrew R; Strand, Øivind; Foucher, Eric (Elsevier BV, 2016)
The European fisheries for Pecten maximus, Aequipecten opercularis, Mimachlamys varia and Chlamys islandica are among the best-studied scallop fisheries worldwide. This chapter provides a current perspective of the scientific research related to the four species and their fisheries, covering biology, physiology, ecology, fishery statistics, management and current developments in the Isle of Man, United Kingdom, Norway, France, Spain, Iceland and Greenland.The history of these fisheries demonstrates expansion, 'boom and bust' and terminal decline; processes still evident today. Despite their economic importance and good underlying scientific knowledge, the fisheries are often data poor regarding stock status and are typically poorly managed, despite a large number of regulations and control measures. Significant issues remain regarding entry restrictions, effort control, stock conservation and spatial management.Scallop recruitment processes are inherently unpredictable, and the subsequent complex relationship with fisheries stock status has led to experiments with closed areas to protect high-density broodstock areas, boost reproductive output and protect settlement habitats and biodiversity. Larger scale interactions between fisheries and spatial management, both positive and negative, are likely in the near future, as the EU Habitats Directive requires the establishment of marine protected areas for habitat and biodiversity features under the Natura 2000 initiative. While this will restrict the largely open access enjoyed by scallop fishermen, closed areas, as sanctuaries for scallops, and with proven fishery benefits, are likely to be beneficial for fisheries in the longer term.The general expansion of effort and vessel capacity in European scallop fisheries, the nomadic nature of larger classes of vessel and the lack of coordinated management, particularly in the United Kingdom, has led to more locally based co-management, especially in inshore areas. This has the potential for greater resource stewardship and the promotion of more sustainable fisheries and stock conservation strategies.Consumer demand for sustainably produced seafood is driving improved management; this is particularly important given the relatively poor sustainability credentials of European scallop fisheries. Some fisheries have achieved recognition of their current management practices, but it requires significant long-term commitment by all stakeholders to gain and retain certification. It seems likely that such efforts will need to become more common if better economic returns and security for fishermen are to be achieved.Diver-based and local-management solutions may represent alternatives for large-scale dredge-dominated fisheries, but ultimately European scallop fisheries must adopt a longer term and more responsible approach. © 2016 Elsevier B.V.